Formation of Linguistic Professionalism for Students of Non- Specialized Departments at Taibah University: personification and processing in The Light of Introduction to Linguistic Skills - Haji, Khadijah Mohammed (Journal of Educational and Psychological Sciences, 2020)
The study aimed to determine the degree of inclusion of both Arabic language skills courses [1] and [2], skills that necessary to form linguistic professionalism among students of departments other than specialization at Taibah University and to present a proposed vision for developing both courses in the introduction of language skills. To achieve this, the study followed the descriptive analytical approach; so a list was built that includes 6 skills: Listening, speaking, reading, writing, grammar, and a branch of these skills include 119 skills. In the light of this list, a content analysis card was designed and after verification of its credibility and stability, it was applied in the second semester of the university year (1441H/2020) on The study’s community, which consists of descriptions and books of Arabic language skills [1] and [2], and the branches of analysis reached 10 branches, which included 275 units of analysis, and statistical data processing results have resulted in relative ratio differences in skills provided by two courses, and that they do not integrate skills needed to form Arabic Language Professionalism in non- specialized students; only two skills were received from listening, as same as syntax skills, and the number of speaking skills was limited to 5 skills, while 13 in reading skills, 15 in writing skills, and 36 in grammar skills. In the light of the outcomes, suggestions were provided to develop the two courses with the benefit of the introduction of language skills; balancing conceptual knowledge with language skills; focusing on linguistic practice in listening, reading, speaking and writing; and some of the recommendations and proposed research.
Keywords: Formation linguistic professionalism; Arabic language skills; students of non- specialized departments; Arabic language skills curriculum [1]; Arabic language skills curriculum [2]